Primary Cerebral Hydatidosis in a Child: A Case Report with a Rare Site of Occurrence - Shahid Iftekhar Sadique; Shivam Chakraborty; Chhanda Das; Mamata Guha Mallick Sinha (JCDR Research and Publications Pvt. Ltd., 2022)
Hydatid cyst of brain in an extremely rare entity. A case of primary hydatidosis of brain without any involvement of other areas is even rarer. Most commonly involved areas are liver and lung because of rich vascularity and vicinity to portal circulation. Central Nervous System (CNS) or most importantly cases of hydatid cysts of brain are very rare. This case report is about a 7-yearold girl, from eastern India, who presented with multiple hydatid cysts in cranial cavity. She presented with headache, sudden loss of balance, short time memory loss. On Magnetic Resonanace Imaging (MRI), multiple cystic lesions were noted in cranial cavity. Magnetic Resonance (MR) Spectroscopy findings were suggestive of hydatid disease. These cysts were removed through neurosurgical intervention. The diagnosis was confirmed by gross and microscopic examination. Importance of keeping hydatidosis as a differential diagnosis while working up cases of cystic Space-occupying Lesion (SOL) of the brain in children is evident here.